Hubungan Kausalitas antara Kinerja Sosial dan Ekonomi Perusahaan - Paulina Permatasari (Faculty of Economics and Business, University of Pasundan, 2013)
The purpose of this study is to investigate the causality of relationship between the corporate economic performance and corporate social performance and also to get a picture about disclosure of Corporate Social Reporting (CSR) performance of companies in Indonesia that have deployed and published Standalone Sustainability Reports, and/or has disclosed Social and Environmental Responsibility or Sustainability in Annual Report, and the company website. The variables used to measure corporate economic performance are company size, profitability, leverage, and growth. The corporate social performance is measured by using an CSR disclosure index. The Causality relationship between corporate economic and social performance is based on the Slack Resource Theory and Good Management Theory. As the pilot study, a sample of 34 companies listed on JSX is taken using stratified random sampling method with 2010 data as the focus of the report analysis. The result of this study shows that there’s no significant relationship between Corporate Economic and Corporate Social Performance. The study also shows the low level of corporate disclosure of CSR.